SLC1A3 contributes to L‐asparaginase resistance in solid tumors. (16th September 2019) - Sun, Jianhui; Nagel, Remco; Zaal, Esther A; Ugalde, Alejandro Piñeiro; Han, Ruiqi; Proost, Natalie; Song, Ji‐Ying; Pataskar, Abhijeet; Burylo, Artur; Fu, Haigen; Poelarends, Gerrit J; van de Ven, Marieke; et al.
Abstract: L‐asparaginase (ASNase) serves as an effective drug for adolescent acute lymphoblastic leukemia. However, many clinical trials indicated severe ASNase toxicity in patients with solid tumors, with resistant mechanisms not well understood. Here, we took a functional genetic approach and identified SLC1A3 as a novel contributor to ASNase resistance in cancer cells. In combination with ASNase, SLC1A3 inhibition caused cell cycle arrest or apoptosis, and myriads of metabolic vulnerabilities in tricarboxylic acid (TCA) cycle, urea cycle, nucleotides biosynthesis, energy production, redox homeostasis, and lipid biosynthesis. SLC1A3 is an aspartate and glutamate transporter, mainly expressed in brain tissues, but high expression levels were also observed in some tumor types. Here, we demonstrate that ASNase stimulates aspartate and glutamate consumptions, and their refilling through SLC1A3 promotes cancer cell proliferation. Lastly, in vivo experiments indicated that SLC1A3 expression promoted tumor development and metastasis while negating the suppressive effects of ASNase by fueling aspartate, glutamate, and glutamine metabolisms despite of asparagine shortage. Altogether, our findings identify a novel role for SLC1A3 in ASNase resistance and suggest that restrictive aspartate and glutamate uptake might improve ASNase efficacy with solid tumors. Synopsis: While L‐asparaginase is an effective drug for the treatment of childhood leukemia, toxicity and tolerance hamper its further usage in patients with solid tumors. Here, a genome‐wide functional screen identifies a role for amino acid transporter SLC1A3 in asparaginase resistance in cancer cells, suggesting a therapeutic perspective for restrictive aspartate and glutamate uptake in solid tumors. Loss‐of‐function screen identifies SLC1A3 as facilitator of asparaginase resistance. SLC1A3 is highly expressed in solid tumors. Combined SLC1A3 blockade and asparaginase treatment impair cell growth in vitro and tumorigenesis in vivo . Supplementation of intracellular aspartate and glutamate levels by SLC1A3 promotes cancerogenesis. Abstract : Amino acid transporter SLC1A3 facilitates cancer development by circumventing amino acid deprivation induced by asparaginase treatment.